2021
DOI: 10.1080/03067319.2021.1900144
|View full text |Cite
|
Sign up to set email alerts
|

Environmental geochemical signature of shale in pollution assessment of trace metals in soil and water in parts of southern Benue trough, southeastern Nigeria

Abstract: Black shales have a great environmental geochemical significance and act as a source of metal enrichment which upon weathering could release trace elements into soil system where they are in turn mobilized and release into surface water and groundwater systems. An investigation of environmental geochemistry of rock, soil and water in parts of Abakaliki, southeastern Benue trough, Nigeria was carried out in order to evaluate the impact of shale bedrock in the soil and water environment. Shale rock, soil and wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…In this study, an EF value (EF > 2) was used to estimate the anthropogenic input (AI) of trace elements; hence, the mean EF values depicted slightly to moderate (1 < AI < 50) inputs for Fe, Pb, Zn, and Cd, with Fe, and Cd showing higher enrichment. However, they appear to be negligible anthropogenic inputs for Ba and Mn, implying that these elements were mainly derived from the parent material (Nganje et al, 2021). Hence results from this study have shown that the enrichment of heavy metals in the soil is majorly influenced by anthropogenic activities and to a lesser extent by geogenic controls (from parent material).…”
Section: Contamination Factor (Cf) and Enrichment Factor (Ef)mentioning
confidence: 61%
See 4 more Smart Citations
“…In this study, an EF value (EF > 2) was used to estimate the anthropogenic input (AI) of trace elements; hence, the mean EF values depicted slightly to moderate (1 < AI < 50) inputs for Fe, Pb, Zn, and Cd, with Fe, and Cd showing higher enrichment. However, they appear to be negligible anthropogenic inputs for Ba and Mn, implying that these elements were mainly derived from the parent material (Nganje et al, 2021). Hence results from this study have shown that the enrichment of heavy metals in the soil is majorly influenced by anthropogenic activities and to a lesser extent by geogenic controls (from parent material).…”
Section: Contamination Factor (Cf) and Enrichment Factor (Ef)mentioning
confidence: 61%
“…The high enrichment of Fe in the soil is attributed to weathering of Fe-rich minerals that underlie the area. Moreover, the chemical weathering of shale is accompanied by the dissolution of clay minerals such as illite and chlorite, and Fe and Al are the common constituents of clay minerals (Reimann et al, 2003, Nganje et al, 2021. The concentration of Ba deflects from 21.34 mg/kg-1 to 65.34 mg/kg-1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations